2022
DOI: 10.3389/fnut.2022.1069760
|View full text |Cite
|
Sign up to set email alerts
|

Could Chlorella pyrenoidosa be exploited as an alternative nutrition source in aquaculture feed? A study on the nutritional values and anti-nutritional factors

Abstract: This work attempted to identify if microalgal biomass can be utilized as an alternative nutrition source in aquaculture feed by analyzing its nutritional value and the anti-nutritional factors (ANFs). The results showed that Chlorella pyrenoidosa contained high-value nutrients, including essential amino acids and unsaturated fatty acids. The protein content in C. pyrenoidosa reached 52.4%, suggesting that microalgal biomass can be a good protein source for aquatic animals. We also discovered that C. pyrenoidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…These nutrients are fundamental for the growth, development, and overall well-being of aquatic life. Proteins are crucial for growth, and microalgae offer a plentiful supply of high-quality proteins, containing a diverse range of essential amino acids necessary for protein synthesis and physiological functions (Chen et al, 2022). Omega-3 fatty acids like eicosapentaenoic acid and docosahexaenoic acid are essential for aquatic organisms' growth, reproduction, and overall health, with microalgae being a primary source in aquatic ecosystems (Fang et al, 2022).…”
Section: Microalgae As a Natural Source Of Essential Nutrients For Aq...mentioning
confidence: 99%
See 1 more Smart Citation
“…These nutrients are fundamental for the growth, development, and overall well-being of aquatic life. Proteins are crucial for growth, and microalgae offer a plentiful supply of high-quality proteins, containing a diverse range of essential amino acids necessary for protein synthesis and physiological functions (Chen et al, 2022). Omega-3 fatty acids like eicosapentaenoic acid and docosahexaenoic acid are essential for aquatic organisms' growth, reproduction, and overall health, with microalgae being a primary source in aquatic ecosystems (Fang et al, 2022).…”
Section: Microalgae As a Natural Source Of Essential Nutrients For Aq...mentioning
confidence: 99%
“…Additionally, microalgae contain other valuable lipids, such as monounsaturated and polyunsaturated fatty acids, critical for energy storage, membrane structure, and various physiological processes in aquatic organisms (Yaakob et al, 2014). The nutritional composition of microalgae can be optimized through cultivation strategies, offering tailored nutrient profiles for different aquaculture species (Chen et al, 2022). Cultivating microalgae using sustainable methods underscores their potential as an eco-friendly solution to meet the nutritional needs of aquatic organisms in aquaculture, further promoting sustainability (Chacón-Lee & González-Mariño, 2010;Kumar et al, 2020).…”
Section: Microalgae As a Natural Source Of Essential Nutrients For Aq...mentioning
confidence: 99%
“…Aquaculture is viewed as a sustainable approach to extend depleted fish populations and endangered fish types, preserve them, and close the gap between supply and demand for aquatic food [1][2][3]. Aquaculture operations productivity is affected by a number of interconnected aspects, including the aquatic environment, nutrition, and the farmed stock [4][5][6]. Maximizing these factors is the foundation of sustainable aquaculture [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that microalgae can effectively improve the immune function and growth of the cultured animals, thereby increasing the efficiency of aquaculture [ 4 , 5 ]. Among them, Chlorella pyrenoidosa , belonging to the genus Chlorella , phylum Chlorophyta, is widely used in feed addition in aquaculture because of it contains a variety of unsaturated fatty acids, proteins, carotenoids, biological polysaccharides, minerals, and other metabolites [ 6 ]. Therefore, the exogenous microalgae addition can achieve the dual effects of regulating water quality and promoting the growth of the cultured animals, thereby providing an effective way to promote sustainable development of freshwater aquaculture.…”
Section: Introductionmentioning
confidence: 99%